1967
DOI: 10.1002/1097-0142(196711)20:11<1871::aid-cncr2820201112>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Response of men with advanced prostatic carcinoma to exogenous administration of testosterone

Abstract: Twenty‐six men in whom the diagnosis of prostatic carcinoma had been established recently and ten men with prostatic carcinoma in relapse after orchiectomy were administered testosterone propionate. Of the measures of tumor activity that were made the only objective alteration was in the serum acid phosphatase; however, in both groups of patients the response to testosterone was extremely variable. None of the ten men in relapse experienced complete objective remission although one man, who was preterminal, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
3

Year Published

1969
1969
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 11 publications
1
62
0
3
Order By: Relevance
“…There are reports of so far inexplicable responses of prostatic carcinoma patients to administration of testosterone (Brendler et al, 1950;Prout & Brewer, 1967;Crowin et al, 1970). In rare cares, testosterone along led to objective improvement of the patient's condition.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of so far inexplicable responses of prostatic carcinoma patients to administration of testosterone (Brendler et al, 1950;Prout & Brewer, 1967;Crowin et al, 1970). In rare cares, testosterone along led to objective improvement of the patient's condition.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] More contemporary clinical trials have shown little, if consistent evidence of a carcinogenic influence or the tendency to 'unmask' subclinical prostate cancer when TRT is prescribed to otherwise healthy hypogonadal men. [4][5][6] On the basis of lingering concerns and uncertainly, coupled with the fact that the prostate is known to be a androgensensitive organ, most evidence-based clinical guidelines recommend close surveillance of the prostate with prostate-specific antigen (PSA) and digital rectal examination among men treated with TRT.…”
Section: Introductionmentioning
confidence: 99%
“…This publication and subsequent reviews and presentations led to the conventional wisdom that testosterone could cause prostate cancer, and that TRT could either induce de novo prostate cancer or unearth an occult prostate malignancy. 3,4 Indeed, an international survey published in 2007 showed that as many as 70% of healthcare providers were concerned about the association of TRT and prostate cancer. …”
Section: Wwwtrendsinmenshealthcom Trends In Urology and Men's Health mentioning
confidence: 99%